Pengaruh Viral Marketing, Influencer Marketing dan Live Streaming Shopping terhadap Keputusan Pembelian pada TikTok Shop di Kota Semarang - Azka Haikal Wicaksana; Imam Nuryanto (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This study aims to determine the effect of Viral Marketing, Influencer Marketing and Live Streaming Shopping on Purchasing Decisions at TikTok Shop in Semarang City. The population in this study are TikTok users and have purchased products at TikTok Shop. The number of samples used was 100 respondents and sampling using purposive sampling technique. The research data was subjected to multiple linear regression tests using SPSS software. The results of this study indicate that: (1) Viral Marketing has a significant positive effect on Purchase Decisions, (2) Influencer Marketing has a significant positive effect on Purchase Decisions, (3) Live Streaming Shopping has no significant effect on Purchase Decisions